A study on the factors that cause delay in issuing insurance certificate of construction insurance at PNSB Insurance Brokers Sdn. Bhd. (PIBSB) / Muhammad Akmal A. Halim - A. Halim, Muhammad Akmal (Faculty of Business and Management, 2011)
This study was designed to uncover the real factors that cause delay in issuing insurance certificate of construction insurance at PNSB Insurance Brokers Sdn. Bhd. (PIBSB). Issuing certificate of insurance is such a basic in insurance industry. In this study, the methods used are questionnaire and personal interview to identify the relevant information regarding the study on the factors that cause delay in issuing insurance certificate of construction insurance. This study will reveal the real problem and challenging situation faced by PNSB Insurance Brokers Sdn. Bhd. Secondary data that been used in this study come from journals, references books, previous thesis and internal data.